Heidelberg interaction training for language promotion in early childhood settings (HIT) - Buschmann, Anke; Sachse, Steffi (European journal of education, 2018)
Beside parents, teachers in early childhood education and care have the greatest potential to foster language acquisition in children. This is especially important for children with language delays, language disorders or bi-/multilingual children. However, they present teachers with a particular challenge in language support. Therefore, integrated language facilitation programmes are needed to promote language acquisition in the daily routine of daycare facilities and kindergartens. In this article, the Heidelberg Interaction Training for Language Promotion in Early Childhood Settings (HIT) is presented as a systematic approach to improve daily interactions between preschool teachers and children. This group training comprises six half-day sessions over a period of six months. The objective is to expand teachers’ knowledge about language development in general and more specifically regarding children with language problems or bi-/multilingual children. Furthermore, teachers learn a responsive interaction style and various strategies of language modelling by means of video supervision and feedback. Teachers’ satisfaction with the training has been evaluated and its efficacy in terms of changes in their behaviour and children's language performance has been proven in several intervention studies and meta-analytic reviews. Lastly, implementation considerations for lasting effects following the HIT are discussed.
Gesehen am 04.02.2020